Analisis Permintaan Minyak Goreng di Kota Banda Aceh - Murtala - (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
The purpose of this study was to determine the effect of cooking oil price, substitute prices, income and population to the demands of cooking oil in the city of Banda Aceh and magnitude of price and income elasticity of demand for cooking oil in the city of Banda Aceh. Measurement of the request made by linear Marshallian demand function (Marshalian Linear Demand Function). This study uses time series data starting from 1980 to 2003. The type of data is secondary data obtained from Connecticut, and Department of Trade and Industry and other related agency. Data were analyzed with OLS approach (Ordinary Least Square). Demand function estimation results show satisfactory results. This is evident both from the testing of universal and partial, in which all independent variables in this study significant effect on demand for cooking oil. In addition, the estimated elasticity coefficients have the elasticity <1, in accordance with the expected theory. Based on estimates of the price variables have negative and substitute prices, income and population have positive influence on demand is inelastic and cooking oil, it is also in accordance with the theory. Koefiien determinant (R2) equal to 98.03%, which means the independent variable consisting of variable oil price, substitute price, population and income affect the demand for cooking oil by 98.03% and the rest of 1.97% influenced by other variables.Keywords: Demand Analysis